Development, yield and chemical composition of the first ratoon sugar cane as a function of phosphorus sources - Pasuch, Bruno D’orazio; Caione, Gustavo; Rodrigues, Marcos; Drescher, Alexander Hugo; Fernandes, Francisco Maximino (Comunicata Scientiae, 2012)
The aim of this study was to evaluate the development, yield and chemical composition of thefirst ratoon sugar cane, depending on the residual effect of phosphorus sources. The study wasconducted in the municipality of Alta Floresta - MT. The experimental design was randomized blocksin factorial scheme 4x2, with four replications. The phosphorus sources were used: bone meal, Aradphosphate and triple superphosphate, and a control without the application of the nutrient. Thevarieties of sugar cane were planted IAC86-2480 and SP79-1011. We evaluated the plant height,stalk diameter, mass of a plant, number of stems, dry matter yield, P content of the plant and thechemical composition of the forage. The residual effect of fertilization, using different sources ofphosphorus, no significant alterations in the development, yield and chemical composition of thefirst ratoon sugar cane, with little reduction in NDF and ADF when using the bone meal. The varietyIAC86-2480 showed better results, providing a higher content of crude protein and phosphorus in theplant and increased production of dry mass.